ҐЕНЕЗИС КРАДІЖКИ У КРИМІНАЛЬНОМУ ПРАВІ УКРАЇНИ - Приходько, Андрій Андрійович (SUPREMANCE OF LAW, 2017)
The article states that only after Ukraine became an independent state in 1991, all branches of legislation received a new vector of development. The long, laborious work of normative makers, which resulted from not only one edition of criminal legislation, led to the appearance in 2001 of the current Criminal Code of Ukraine. During the entire operation of the above-mentioned normative legal act, most of its norms were text-edited, which can be explained by technical progress and, consequently, by the increase in the level of crime and the acquisition of more professional forms. However, despite this, the definition of theft as a secret theft of someone else’s property has not changed.
Keywords: theft; countryside; prevention; history; development; period